The Development of Business Incubators in Universities in Building Business Start-Ups: Systematic Literature Review (SLR) - Adelia Rahma; Sudarmiatin Sudarmiatin (Pusat Riset dan Inovasi Nasional, 2023)
One place for students who want to learn about entrepreneurship through entrepreneurship learning with a business incubator. Entrepreneurship learning in tertiary institutions through business incubators is expected by the Indonesian government in building Start-Ups. especially college. The purpose of this study was to determine the effectiveness of entrepreneurship learning through business incubators in building start-ups in tertiary institutions. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the management of business incubators in tertiary institutions has been going well, this can be proven by the existence of an organizational structure, the proper management of business incubators according to their duties and responsibilities, facilities and infrastructure that are quite complete, and various different types of programs. work with the same goal of growing strat-up souls. The role of the business incubator in cultivating young strat-ups in college is quite good. The results of this research have implications for two things. First, universities are expected to continue to upgrade entrepreneurship learning in a creative, innovative and adaptive manner. Second, the government is expected to continue to improve and equip incubator facilities evenly and improve mentoring/training programs for students